Human immunodeficiency virus type 1 pol gene mutations which cause decreased susceptibility to 2',3'-dideoxycytidine. - Fitzgibbon, J E (1992)
To investigate whether human immunodeficiency virus type 1 pol gene mutations are selected during prolonged 2',3'-dideoxycytidine (ddC) therapy, we used the polymerase chain reaction to amplify a portion of the reverse transcriptase segment of the pol gene from the peripheral blood mononuclear cell DNA of a patient with AIDS before and after an 80-week course of ddC therapy. The consensus sequence from the second sample contained a unique double mutation (ACT to GAT) in the codon for reverse transcriptase amino acid 69, causing substitution of aspartic acid (Asp) for the wild-type threonine (Thr). A mutation (ACA to ATA) also occurred in the codon for position 165, causing substitution of isoleucine (Ile) for Thr. The GAT (Asp) codon was introduced into the pol gene of a molecular clone of human immunodeficiency virus via site-directed mutagenesis. Following transfection, mutant and wild-type viruses were tested for susceptibility to ddC by a plaque reduction assay. The mutant virus was fivefold less susceptible to ddC than the wild type; cross-resistance to 3'-azido-3'-deoxythymidine or 2'3'-dideoxyinosine was not found. The Ile-165 mutation did not confer additional ddC resistance. The Asp-69 substitution may have contributed to the generation of resistant virus in this patient.